Physical Sciences Reviews (De Gruyter, 2016)
Physical Sciences Reviews publishes review articles in the areas of chemistry, physics and materials science. It aims at interdisciplinary topics in or between those classical disciplins. A focus lies on applications, closing the gap towards electrical engineering, bio-engineering and industrial chemistry. Topics Nanotechnology Materials characterization Unit operations Biomaterials Catalysis Chemical reactor technology Trace analytics Article formats Expert reviews